Garantias do servi??o superiores: constru????o e valida????o de uma nova escala servguarantee - Oliveira, Alessandro Silva de (2016)
Services have unique characteristics such as intangibility, present a performance or human action usually produced and consumed in real time and in the customer presence. These singularities make them more complex, making it difficult to standardize and superior quality. Therefore, ensuring the services becomes difficult, but it does not mean that consumer satisfaction can not be guaranteed. In this perspective, Hart (1988) considers that a superior service guarantee can help a business in many ways, but it is necessary to present a guarantee with some essential features such as absoluteness, an easy understanding and communication, meaning and expressiveness, easy claim and a quickly reception. Although several authors consider these features important, validated scales were not properly developed to measure them. Thus, the objective in this thesis is to construct and validate a measurement tool that captures consumer perception on the Service Guarantees, based on five superior characteristics proposed by Hart (1988.1990). To achieve this goal, was created a methodology consists of six steps that will compose the process of construction and validation of a measurement tool. The work included a qualitative phase and other quantitative. The results of the qualitative phase were consistent with the theory, reinforcing the idea that Superior Services Guarantees (GSS) can be better understood through five subcategories or proxies. Based on theory and qualitative research, variables were developed for each of the first order construct that reflect the GSS. In the final collecting data were obtained 367 valid respondents and, at this stage, we used a modeling technique of structural equation and PLS-SEM method for data analysis. In this way, it was verified the reliability of the GSS scale by Load Factor (??), the Composite Reliability and Cronbach Alpha (??). Then were held Convergent Validity, that uses the Average Variance Extracted (AVE), and Discriminant Validity. These tests have proven robust, confirming the reliability of the scale. The nomological validity had two models that confirmed a good adjustmentof the construct GSS in a relationships network with the constructs Perceived Quality and Satisfaction, giving strength and consistency for the validation scale process, which now has the ServGuarantee denomination. Therefore, it is expected that this thesis is useful both in academia, enabling new studies involving ServGuarantee scale, as for managers looking to satisfy its customers and to improve the efficiency of the guarantees of their business service.